Preparation, Immunogenicity, and Protective Efficacy, in a Murine Model, of a Conjugate Vaccine Composed of the Polysaccharide Moiety of the Lipopolysaccharide of Vibrio cholerae O139 Bound to Tetanus Toxoid - Boutonnier, Alain (American Society for Microbiology, 2001)
The epidemic and pandemic potential of Vibrio cholerae O139 is such that a vaccine against this newly emerged serogroup of V. cholerae is required. A conjugate made of the polysaccharide moiety (O-specific polysaccharide plus core) of the lipopolysaccharide (LPS) of V. cholerae O139 (pmLPS) was prepared by derivatization of the pmLPS with adipic acid dihydrazide and coupling to tetanus toxoid (TT) by carbodiimide-mediated condensation. The immunologic properties of the conjugate were tested using BALB/c mice injected subcutaneously three times at 2 weeks interval and then a fourth time 4 weeks later. Mice were bled 7 days after each injection and then once each month for the following 6 months. LPS and TT antibody levels were determined by enzyme-linked immunosorbent assay using immunoplates coated with either O139 LPS or TT. Both pmLPS and pmLPS-TT conjugate elicited low levels of immunoglobulin M (IgM), peaking 5 weeks after the first immunization. The conjugate elicited high levels of IgG antibodies, peaking 3 months after the first immunization and declining slowly during the following 5 months. TT alone, or as a component of conjugate, induced mostly IgG antibodies. Antibodies elicited by the conjugate recognized both capsular polysaccharide and LPS from V. cholerae O139 and were vibriocidal. They were also protective in the neonatal mouse model of cholera infection. The conjugation of the O139 pmLPS, therefore, enhanced its immunogenicity and conferred T-dependent properties to this polysaccharide.